THE EFFECT OF ENVIRONMENTAL ACCOUNTING DISCLOSURE AND ENVIRONMENTAL PERFORMANCE ON FINANCIAL PERFORMANCE OF BANKING COMPANIES - Friska R. Mile; Mahdalena; Ronald S. Badu (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to examine the effect of environmental accounting disclosure and environmental performance on the financial performance of banking companies listed on the Indonesia Stock Exchange during the period 2019–2023. This research employs a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample consists of eight banking companies selected through purposive sampling. Financial performance is measured using Return on Assets (ROA), environmental performance is measured using the Sustainable Banking Assessment (SUSBA) index, and environmental accounting disclosure is measured using the Environmental Disclosure Index (EDI). The data are analyzed using multiple linear regression analysis after passing classical assumption tests. The results indicate that environmental accounting disclosure has a positive and significant effect on financial performance. In addition, environmental performance also has a positive and significant effect on financial performance. These findings suggest that transparent environmental disclosure and the implementation of sustainable banking practices contribute to improved financial performance. Therefore, banking companies are encouraged to enhance environmental accounting disclosure and strengthen environmental performance as part of their sustainability strategy.